Compact Solar Elevator - Samion, Norhafiza; Gia Yi, Sim; Sivalingam, Arcanaa; Sheikh Badredden, Sheikh Ahmad Lutfi (Multidisciplinary Applied Research and Innovation, 2020)
The elevator facilitates disable person to move and it easy to carry heavy things between the floors. However, the environment is getting serious considering activities that help to sustain fossil energy. Energy from the solar truly an alternative to counting on. That is how this project presents the elevator with some aspects concerning the solar cells as an alternative to producing energy by direct conversion of the solar light into electricity. This designed elevator using a set of pulley powered by the hybrid battery bank and supporting by the solar cell array as the recharging power supply. Experimental studies of this model measure the voltage collected from the solar panel during daylight and the pulley response with loads is carried out to compare the energy consumption. Finally, as a conclusion the project of a solar elevator successfully function with an alternative energy supply.